Some blood biochemical indices and fertility following treatment of anestrus in Murrah buffaloes - RATHOUR, K K; PANDIT, R K; AGARWAL, R G; QUADRI, M A; SHRIVASTAVA, O P (The Indian Journal of Animal Reproduction, 2023)
The efficacy of some of the hormonal and non-hormonal drugs for the treatment of anestrus, their effect on cenain blood biochemical indices and conception rate in 36 Murrah buffaloes were studied. The overall mean values of calcium, inorganic phosphorus, total protein were 6.09:t0.55 mg per cent/3.18±0.31 mg per cent / 5.75±0.23 g per cent, respectively, in the anestrus animals. The values elevated significantly (P < 0.01) in the post treated animals Ill the ti expreuiOA of esuusto 9.20±0.42 mg per cent, 5.28:t0.25 mg per cent/ 7.46:t0.17 g per cent, respectively. The animals expressing estrus following different treatments were 66.66 per cent within the duration of 9.60:t:2.44 days. The overall conception rate was 65.33 per cent. The maximum number of expressed animals resulted in estrus in PMSG group (83.33%) and 60.00 per cent concentration. The maximum number of animals concejved in GnRH and progesterone treated groups (75.00 per cent), whereas estrus expression in these groups was only 66.66 per cent. In the Lugol’s iodine treated group 50.00 per cent animals expressed estrus and 66.66 per cent of them conceived.